Gerechtigkeitsprobleme im Wohlfahrtsstaat: Besteuerung, wohlfahrtsstaatliche Transfers und die Gerechtigkeit des eigenen Erwerbseinkommens - Stefan Liebig; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
– The article discusses the conflict of goals between fair compensation for performance and equitable support based on need in modern welfare states, which is a subject of controversy in various disciplines. It answers the question of the extent to which this policy problem of modern welfare states, which is an issue at the macrosocial level, also creates individual perceptions of problems of equity. Based on survey results of a theory-driven supplemental survey of the longitudinal study of the German Socio-economic Panel (SOEP), it was investigated how employed persons evaluated their income with respect to the fairness of earnings and what effect welfare state interventions have. An important result of the analyses is the high proportion of persons who considered their earned income to be fair. Only a quarter of those employed in Germany consider their remuneration to be unfair. Thus it appears that the normative conflict of goals between fair compensation for performance and equitable support based on need described in the literature for the macrosocial level does not really exist at the individual level, as the article discusses theoretically with reference to new multidisciplinary work and also demonstrates empirically. An unexpected result of the analyses is that transfer payments by the government cannot compensate for perceptions of unfairness with regard to individual income; openly recognizable transfer payments may be seen as discriminatory.
Keywords: 330